Mammalian ETCHbox homeodomains - Lewin, T D; Royall, A H; Holland, P W H (University of Oxford, 2021)
Homeodomain sequence data used in Lewin, T.D., Royall, A.H. & Holland, P.W.H. Dynamic Molecular Evolution of Mammalian Homeobox Genes: Duplication, Loss, Divergence and Gene Conversion Sculpt PRD Class Repertoires. J Mol Evol (2021) https://doi.org/10.1007/s00239-021-10012-6 For genome sequence data from which these sequences were deduced, see references cited in the above paper.